PECULIARITIES OF THE ORGANIZATION OF MULTI-ETHNIC, CONVENED MAHALLAS DURING THE YEARS OF INDEPENDENCE - Kamilov Abdusalim Abdullayevich (American Journals Publishing, 2023)
The article examines the topical problems of reforming the system of makhallas in Uzbekistan, the peculiarities of organizing the activities of multinational, religious communities and democratic factors in the years of independence, It is narrated on the content of the Mahallabay Working System.
Keywords: Ministry of Mahalla and Family Support, Appeal to Oliy Majlis